Las Piperaceae de Argentina, Bolivia y Chile - Yuncker, Truman George (Lilloa, 2022)
The author reviews the species of Piperaceae from the indicated countries; gives keys to the genera Piper, Pothomorphe, and Peperomia and their species. He describes several new species and redescribes the others with a long list of provenances, adding numerous illustrations.